The Impact of Same versus Different Price Presentation on Travel Choice and the Moderating Role of Childhood Socioeconomic Status. (March 2022) - Giroux, Marilyn; Franklin, Drew; Kim, Jungkeun; Park, Jooyoung; Kwak, Kyuseop
When making travel decisions, consumers are frequently exposed to a multitude of options, including differing price levels for the same product or service across a range of online travel agencies. The current research investigates how the magnitude of price dispersion in online pricing can influence travelers' product evaluations and purchase intentions. Specifically, we predict that travelers will prefer a hotel with no price dispersion to a hotel with different prices listed when the price difference is small, or narrow. However, when the price difference is more pronounced, or wide, travelers will prefer a hotel with price differences compared to a hotel with no price dispersion. Four experiments demonstrate that this effect is consistent across different contexts and categories. Additionally, based on life history theory, we argue that the relative preference for the same versus different price dispersion will be moderated by the travelers' childhood socioeconomic status (SES).